Regenerative pulp therapy for immature nonvital teeth with plasma-rich fibrin - Amitava Bora; Shabnam Zahir; Gautam Kumar Kundu; Abhirup Goswami (SRM Journal of Research in Dental Sciences, 2015)
Regenerative endodontics is a biologically based procedure designed to replace damaged structures such as dentin, root structures, and cells of the pulp dentin complex. Regeneration of dental tissue is possible from a variety of pre existing dental stem cells in a properly disinfected root canal system in the presence of suitable growth factors and scaffold medium. Platelet-rich plasma or platelet-rich fibrin act as ideal three-dimensional scaffold medium and a rich source of growth factors that favors from stem cell multiplication and differentiation. The present case report presents a case of regenerative endodontic procedure in a 11-year-old male child with necrotized 31 and 41 with large periapical radiolucency and extra oral discharging sinus where plasma-rich fibrin has been used as scaffold and a source of growth factors.